The Effect of Project Based Learning Model and Learning Styles on Students’ Learning Outcomes - Azhar, Imam; Badriyah, Lailatul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
The purpose of this study was to test the differences in the application of project- based learning methods assisted by audio-visual media versus exposure methods in science subjects for grade V who have different learning styles at MI Mazroatul Ulum Lamongan. This study used a quasi-quantitative experimental approach with a 2×3 factorial design type. The subjects of the study were grade V (five) students who were divided into experimental and control groups. Data collection used observation, tests, and questionnaires. The data analysis techniques used were Independent Sample T-Test, One-way Anova, dan Two-way Anova. The results of the study showed: a) there were differences in learning outcomes of students taught using the project-based learning method and demonstration method, b) the grade V students had varied learning styles (visual, auditory, and kinesthetic), c) there were differences in learning outcomes on students who had different learning styles. and d) there was no interaction effect of the use of different methods on students’ learning outcomes who had different learning styles. Therefore, further research is very possible to be carried out to explore the things that cause the interactive influence. It is very possible to explore this research by looking for other variables that are assumed to be able to provide an interactive influence.